2013
DOI: 10.1039/c3cc43269f
|View full text |Cite
|
Sign up to set email alerts
|

[CoI(CN)2(CO)3]−, a new discovery from an 80-year-old reaction

Abstract: A systematic study of the 80-year-old simple and fundamental reaction of cobalt(II) salt with cyanide under one atmosphere CO was carried out and two novel Co(I) complexes were isolated in the absence of hydroxide. These complexes are the first structurally characterized mixed cobalt CO-CN(-) compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…27 Recently, two kinds of cobalt complexes with mixed cyanide-carbonyl ligands were determined using single crystal X-ray diffraction. 28 By employing pure rotational spectroscopy experiments 22 and ab initio calculations, 23 cobalt cyanide was determined to be a linear CoCN structure.…”
Section: Introductionmentioning
confidence: 99%
“…27 Recently, two kinds of cobalt complexes with mixed cyanide-carbonyl ligands were determined using single crystal X-ray diffraction. 28 By employing pure rotational spectroscopy experiments 22 and ab initio calculations, 23 cobalt cyanide was determined to be a linear CoCN structure.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the reaction between cobalt(2+) salt and 4 equivalents of cyanide under 1 atmospheric CO in aqueous solution yielded Co I (CN) 2 (CO) 3 À and Co III (CN) 6 3À through disproportionation. 6 We have now expanded our study to nickel systems. Unlike cobalt, the carbonylation of the nickel(2+) salt in neutral aqueous solution with 1 to 3 equivalents of cyanide did not yield any CO-containing product.…”
mentioning
confidence: 99%
“…The addition of PPh 4 Cl to the colorless reaction mixture followed by CH 2 Cl 2 extraction led to the isolation of (PPh 4 )[Ni(CN)(CO) 3 ] as a white solid in good yield. 6 ‡ From the amount of NiCl 2 , NaCN, CO used and the amount of Ni 0 (CN)(CO) 3 À , BaCO 3 generated, the carbonylation of nickel(2+) with 1 equivalent of cyanide in alkaline solution can be expressed in reaction (1):…”
mentioning
confidence: 99%